1992
DOI: 10.1002/jbt.2570070409
|View full text |Cite
|
Sign up to set email alerts
|

The differential hepatotoxicity and cytochrome P450 responses of fischer‐344 rats to the three isomers of dichlorobenzene

Abstract: The acute hepatotoxicity and response of hepatic cytochrome P450 to treatment with the three isomers of dichlorobenzene (DCB) have been investigated. The objectives were to estimate the onset of toxicity and to further elucidate the role of cytochrome P450 in the metabolism and toxicity of these compounds. In a study design employing one animal per dose level, Fischer-344 rats were gavaged with up to 25 different dosages, then evaluated 24 h later. Hepatic necrosis, serum alanine aminotransferase, and serum as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Hissink et al 20) reported that total in vitro conversion of p-DCB into covalently bound, reactive metabolites by liver microsomes was in the descending order of mouse> rat, and that reactive metabolites such a s 2 , 5 -d i c h l o r o h y d r o q u i n o n e a n d 2 , 5 -dichlorobenzoquinone were produced more in mice than in rats. Allis et al 36) showed that the severity of hepatotoxicity induced by o-, m-and p-DCB was in the descending order of o-> m-> p-DCB, and was closely associated with the rank order of the hepatic P-450 responses to these three isomers. Therefore, it can be inferred from these results that the large species difference in hepatotoxicity seen in this study is attributable to a difference in the metabolic capacity of p-DCB of the liver P-450 between rats and mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hissink et al 20) reported that total in vitro conversion of p-DCB into covalently bound, reactive metabolites by liver microsomes was in the descending order of mouse> rat, and that reactive metabolites such a s 2 , 5 -d i c h l o r o h y d r o q u i n o n e a n d 2 , 5 -dichlorobenzoquinone were produced more in mice than in rats. Allis et al 36) showed that the severity of hepatotoxicity induced by o-, m-and p-DCB was in the descending order of o-> m-> p-DCB, and was closely associated with the rank order of the hepatic P-450 responses to these three isomers. Therefore, it can be inferred from these results that the large species difference in hepatotoxicity seen in this study is attributable to a difference in the metabolic capacity of p-DCB of the liver P-450 between rats and mice.…”
Section: Discussionmentioning
confidence: 99%
“…The ingested p-DCB goes through the liver during the first pass after the gastro-intestinal absorption, whereas the inhaled p-DCB is absorbed into the lung, distributed through the bloodstream to various organs, including the liver and adipose tissue. Since the absorption rate of p-DCB was comparable for the lung (33%) 38) and for the gastro-intestinal tract (55 %) 40) , and since the covalently bound, reactive metabolites were reported to be responsible for the hepatoxicity 20,36) , it is likely that the first pass effect by the oral intake enhances p-DCBinduced hepatotoxicity compared to inhalation exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Acute liver damage, as assessed by histopathology and serum enzyme/biochemical indicators following gavage exposure, was not induced by high levels of p-dichlorobenzene in rat given single doses of ≤2790 mg/kg (Allis et al, 1992), rats and mice given single doses of ≤1200 mg/kg/d (Eldridge et al, 1992), or rats and mice administered ≤300 and ≤600 mg/kg/day, respectively, 5 d/week for 1 week (Lake et al, 1997). Porphyria, manifested as markedly elevated porphyrin levels in the liver and urine and suggestive of hepatic damage, was reported in rats that were orally exposed to 770 mg/kg/d for 5 d (Rimington & Ziegler, 1963).…”
Section: P-dichlorobenzenementioning
confidence: 99%
“…Human hepatic cytochrome P450 isoenzymes which can metabolize DCB to 2,5-dichlorophenol include CYP1A2 and CYP2E1 (Bogaards et al, 1995). Studies into the acute toxicity of DCB and its isomers have demonstrated that 1,2-dichlorobenzene is more toxic to rat and mouse liver and to rat kidney than 1,3-dichlorobenzene and DCB (Allis et al, 1992;Valentovic et al, 1993;Umemura et al, 1996).DCB is considered to be a nongenotoxic agent as demonstrated by results of a number of short-term tests for mutagenic and genotoxic potential (Loeser and Litchfield, 1983; NTP, 1987;Steinmetz et al, 1988). The carcinogenicity of DCB has been evaluated in a 2-year study in F344 rats and B6C3F, mice (NTP, 1987).…”
mentioning
confidence: 99%
“…Human hepatic cytochrome P450 isoenzymes which can metabolize DCB to 2,5-dichlorophenol include CYP1A2 and CYP2E1 (Bogaards et al, 1995). Studies into the acute toxicity of DCB and its isomers have demonstrated that 1,2-dichlorobenzene is more toxic to rat and mouse liver and to rat kidney than 1,3-dichlorobenzene and DCB (Allis et al, 1992;Valentovic et al, 1993;Umemura et al, 1996).…”
mentioning
confidence: 99%